Valuation Inaccuracy: Implication on Commercial Property Investment Performance in Akure, Nigeria - Eziukwu, Nwosu Akuakanwa (Journal of African Real Estate Research, 2019)
Issues of valuation error have become one of the most significant challenges of the valuation profession lately. The derivation of property returns from commercial income and prices actually paid has cast a lot of doubt on the reliability of valuation opinion in the commercial property investment decision process. This study investigates the implication of valuation inaccuracy on investment performance of commercial properties in Akure, Nigeria. Questionnaires were administered to 25 registered and practicing Estate Surveyors and Valuers (ESVs) in Akure and 19 duly filled questionnaires were returned for analysis. Descriptive analysis was used to assess the level of inaccuracy and the factors influencing the valuation inaccuracy, while regression analysis was used to examine the effect of this inaccuracy on investment performance. It was discovered that the most common level of valuation inaccuracy in Akure is ±11-15% which is above the acceptable range of ±5%. It was also discovered that the various assumptions made by the valuers and the market indices used in carrying out valuation have the highest influence on the inaccuracy discovered in their valuation. From the simple linear regression analysis carried out, it was found that valuation inaccuracy has negative implication, at β=-.800, t=3.873, p>.05 on the investment performance. This shows that the higher the level of inaccuracy of valuation, the lower the performance of the investment. The result, however, indicates that the effect of valuation inaccuracy on commercial property investment performance is statistically insignificant. This study recommends that valuers in Akure should be very careful in making assumptions and be more vigilant regarding their use of market indices for valuations. It also recommends that valuers should be aware that investors rely on the accuracy of their valuations for making timely investment predictions and should therefore ensure conscientious efforts are put in place for accuracy of their valuations.